Design of Mazzilli’s Zero Voltage Switching (ZVS) Circuit as Plasma Glow Discharge Generator - Anisah Muthi’ah; Amien Rahardjo; Faiz Husnayain; Chairul Hudaya (ELKHA : Jurnal Teknik Elektro, 2020)
Purification water has several methods; one of them is the plasma generation. The circuit used to generate plasma is Zero Voltage Switching (ZVS), where its use uses the resonance circuit concept. The main category to generate plasma glow discharge is the circuit should generate high voltage output with a current range from 10-6 A to 1 A. In this study, when ZVS connected to the flyback converter with an input voltage of 12 V, the output values of 11 kV and 11 μA were obtained. In comparison, if ZVS was not connected to the flyback converter, the circuit is less stable, and the output value is weak because the output values only reach 8.97 kV and 8.97 μA. For maximum output, the ZVS circuit should be connected to the converter circuit due to the flyback converter can repair and strengthen the voltage. The flyback converter circuit is affected by the diode and capacitance effects. The effect of using capacitors in a flyback converter circuit is when the capacitance is too low, the ripple will form. Then when capacitance reaches a specific value, the ripple will decrease, and the voltage graph will approach a straight line. Hence the use of components in the ZVS and the flyback converter need to be considered because it affects how the release of plasma glow discharge will form.